Sustained drag reduction and thermo-hydraulic performance enhancement in textured hydrophobic microchannels. (April 2018) - Dilip, D.; Vijay Kumar, S.; Bobji, M.S.; Govardhan, Raghuraman N.
Highlights: A method to sustain drag reduction in textured hydrophobic microchannels is proposed. Drag reduction is sustained by maintaining trapped air bubbles on the textured surface. Air bubbles are maintained by controlling the temperature of water near the surface. Presence of air bubbles reduce drag, but lower the thermal transport performance. Thermo-hydraulic performance is enhanced when bubbles are flush with the surface. Abstract: Drag reduction obtained on flow over textured hydrophobic surfaces has been ascribed to the presence of entrapped air within the surface micro-texture. To sustain the drag reduction, it is important that the entrapped air be maintained on the surface. However, the entrapped air bubbles tend to shrink with time and finally disappear, causing the drag reduction also to reduce and eventually vanish. Recent research shows that by controlling the absolute pressure of water, it is possible to sustain the entrapped air bubbles on the surface and hence the drag reduction for extended periods of time. In this paper, we explore the possibility of sustaining the entrapped air by varying the absolute temperature of water in the vicinity of the textured surface. For this, the textured surface is externally heated and the evolution in the size of trapped air bubbles with time is observed. Simultaneous pressure and temperature measurements are made along with the visualization, to study the concomitant effects on drag and heat transfer. We find that, varying the absolute temperature influences the trapped air bubble dynamics appreciably, which in turn affects the measured pressure drop across the channel. By varying the external heat input, it was found that the trapped air bubbles can be maintained on the surface for prolonged periods of time, at an optimum size suitable for drag reduction, such that sustained and maximized drag reduction can be achieved. The presence of trapped air bubbles is found to inhibit the heat transfer across the surface. However, when the pressure drop reduction achieved due to the presence of air bubbles is significant enough, the combined thermo-hydraulic performance is found to be enhanced. The results, not only provides important inputs towards achieving sustained drag reduction from textured hydrophobic surfaces, but also ascertains the feasibility of using such surfaces in micro-scale heat transfer applications.